Depressed-Cladding 3-D Waveguide Arrays Fabricated With Femtosecond Laser Pulses - Castillo, Gabriel R.; Labrador-Paez, Lucia; Feng Chen; Camacho-Lopez, Santiago; Vazquez de Aldana, Javier R. (Journal of lightwave technology, 2017)
We report on the fabrication of waveguide arrays based on depressed-cladding structures produced by femtosecond laser direct inscription in a Nd:YAG crystal. The arrays consisted of seven divergent hexagonal waveguides with different separations between the waveguides at the exit of the crystal. Optical characterization in the visible (633 nm) and near infrared (800 nm) was performed. The obtained modal profiles show multimodal behavior in the visible and nearly single-mode at 800 nm. The propagation losses were measured to be 1.6-3.0 dB/cm in all the cases. Microluminescence maps were obtained showing the presence of defects only at the damage tracks and a residual stress that slightly affects the waveguide core in the vicinity of the tracks. This affected area is responsible for a modal profile distortion that can be clearly seen at 633 nm, but does not modify the modal profiles in the near infrared. Our results show a very good performance of the fabricated structures and suggest a promising potential use in photonic applications (i.e., photonic lanterns) that can be easily implemented in other transparent materials.